The Pathogenic Role of the Adaptive Immune Response to Modified LDL in Diabetes - Virella, Gabriel; Lopes-Virella, Maria F. (Frontiers in Endocrinology, 2012)
The main causes of morbidity and mortality in diabetes are macro and microvascular complications, including atherosclerosis, nephropathy, and retinopathy. As the definition of atherosclerosis as a chronic inflammatory disease became widely accepted, it became important to define the triggers of vascular inflammation. Oxidative and other modifications of lipids and lipoproteins emerged as major pathogenic factors in atherosclerosis. Modified forms of LDL (mLDL) are proinflammatory by themselves, but, in addition, mLDLs including oxidized, malondialdehyde (MDA)-modified, and Advanced Glycation End (AGE)-product-modified LDL induce autoimmune responses in humans. The autoimmune response involves T cells in the arterial wall and synthesis of IgG antibodies. The IgG autoantibodies that react with mLDLs generate immune complexes (IC) both intra and extravascularly, and those IC activate the complement system as well as phagocytic cells via the ligation of Fcγ receptors. In vitro studies proved that the pro-inflammatory activity of IC containing mLDL (mLDL-IC) is several-fold higher than that of the modified LDL molecules. Clinical studies support the pathogenic role of mLDL-IC in the development of macrovasccular disease patients with diabetes. In type 1 diabetes, high levels of oxidized and AGE- LDL in IC were associated with internal carotid intima-media thickening and coronary calcification. In type 2 diabetes, high levels of MDA-LDL in IC predicted the occurrence of myocardial infarction. There is also evidence that mLDL-IC are involved in the pathogenesis of diabetic nephropathy and retinopathy. The pathogenic role of mLDL-IC is not unique to diabetic patients, because those IC are also detected in non-diabetic individuals. But mLDL IC are likely to reach higher concentrations and have a more prominent pathogenic role in diabetes due to increased antigenic load secondary to high oxidative stress and to enhanced autoimmune responses in type 1 diabetes.